Inhibition effect of tea tree oil on Listeria monocytogenes growth and exotoxin proteins listeriolysin O and p60 secretion. (3rd November 2016) - Liu, Z.; Meng, R.; Zhao, X.; Shi, C.; Zhang, X.; Zhang, Y.; Guo, N.
Abstract: Listeria monocytogenes ( L. monocytogenes ) is a Gram‐positive bacterium that causes infections in humans. In this study, the effects of tea tree oil (TTO) at subinhibitory concentrations on L. monocytogenes growth and two important exotoxin proteins secreted by L. monocytogenes were researched. Treatment with half of minimal inhibitory concentration of TTO demonstrated very little or no reduction in numbers of viable ATCC 19115 cells. Listeriolysin O (LLO) and p60, were investigated. A listeriolysin assay was used to investigate the hemolytic activities of L. monocytogenes exposed to TTO, and the secretion of LLO and p60 was detected by immunoblot analysis. Additionally, real‐time RT‐PCR was used to analyse the influence of TTO on the transcription of LLO and p60 encoded genes hly and iap respectively. According to our experimental results, we propose that TTO could be used as a promising natural compound against L. monocytogenes and its virulence factors. Significance and Impact of the Study: This is the first report on the influence of subinhibitory concentrations of tea tree oil (TTO) on the secretion of listeriolysin O (LLO) and p60, the critical virulence factors involved in Listeria pathogenesis. The results showed that TTO at 0·25 mg ml −1 reduced the secretion of LLO and p60 to 10 and 34·9% respectively, in addtion, the transcription of hly and iap was reduced to 10 and 4·3% at 0·5 mg ml −1 respectively. We propose that TTO could be used as a promising antimicrobial compound and virulence inhibitor against L. monocytogenes . Abstract : Significance and Impact of the Study: This is the first report on the influence of subinhibitory concentrations of tea tree oil (TTO) on the secretion of listeriolysin O (LLO) and p60, the critical virulence factors involved in Listeria pathogenesis. The results showed that TTO at 0·25 mg ml −1 reduced the secretion of LLO and p60 to 10 and 34·9% respectively, in addtion, the transcription of hly and iap was reduced to 10 and 4·3% at 0·5 mg ml −1 respectively. We propose that TTO could be used as a promising antimicrobial compound and virulence inhibitor against L. monocytogenes .